Religious Beliefs May Reduce the Negative Effect of Psychiatric Disorders on Age of Onset of Suicidal Ideation among Blacks in the United States - Assari, Shervin (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVE: To evaluate the possible interaction between religious beliefs and psychiatric disorders among Black Americans. METHODS: In this study, we used data of 5181 adult Black Americans who had participated in National Survey of American Life (NSAL) from February 2001 to June 2003. Variables such as socio-demographics, religious beliefs, and psychiatric disorders were entered in a Cox regression to determine the possible interaction between psychiatric disorders (0, 1, ≥2) and the subjective religiosity on age of onset of suicidal thought among the participants. Main outcome was age of the first serious suicidal ideation. RESULTS: A dose-dependent effect of number of psychiatric disorders on suicidal ideation was observed. Psychiatric disorders had a higher impact on age of suicidal ideation among those with low self-reported religiosity. CONCLUSION: Religious beliefs may buffer the effect of psychiatric disorders on suicidal thought. Blacks who are less religious and suffer psychiatric disorders are at the highest risk for early suicidal ideation.